The English Patient : 1996 - Minghella, Anthony (USA : Miramax Film, 1996)
At the close of WWII, a young nurse tends to a badly-burned plane crash victim. His past is shown in flashbacks, revealing an involvement in a fateful love affair.
162 mins. , col. ; 2 Discs
Keywords: Love affair -- World war II; World War II -- 1945-